High‐grade salivary gland carcinoma with the ETV6‐NTRK3 gene fusion: A case report and literature review of secretory carcinoma with high‐grade transformation. Issue 6 (13th April 2021) - Asai, Satsuki; Sumiyoshi, Shinji; Yamada, Yosuke; Tateya, Ichiro; Nagao, Toshitaka; Minamiguchi, Sachiko; Haga, Hironori
Abstract : Secretory carcinoma or mammary analog secretory carcinoma is an entity of salivary gland carcinoma that is characterized by the ETV6‐NTRK3 gene fusion. Although it is generally considered to be a low‐grade malignancy, some cases of secretory carcinoma with high‐grade transformation (SCHG) have been reported. We herein describe a case of SCHG composed almost exclusively of the high‐grade component. The patient presented with a growing mass in the buccal mucosa and underwent surgery. Tumor cells showing high‐grade nuclear atypia were arranged in solid or cribriform nests with comedo‐like necrosis. A differential diagnosis included high‐grade salivary gland carcinoma, such as salivary duct carcinoma. Immunohistochemically, tumor cells were focally positive for S‐100 and negative for mammaglobin and showed nuclear positivity for pan‐Trk. A reverse transcription polymerase chain reaction assay showed that the tumor harbored the ETV6‐NTRK3 gene fusion. A histological review of microscopic slides of the tumor did not reveal a typical secretory carcinoma component, except for a very focal area. We ultimately diagnosed this tumor as SCHG. This case underscores the importance of recognizing the histological spectrum of SCHG and the utility of pan‐Trk immunohistochemistry to detect secretory carcinoma, which may be targeted by tyrosine kinase inhibitors.